To simplify the complex fraction, we first need to simplify the numerator and the denominator separately before dividing them.
Numerator: x + (4x/y) = x + (4x/y) = x + (4x/y) = (x * y)/y + (4x/y) = (x * y + 4x)/y = x(y+4)/y = (x/y)(y+4)
Denominator: 7/3x = (7/3)x
Therefore, the simplified complex fraction is:
(x/y)(y+4) / (7/3)x
Simplify the complex fraction.
x +(4x/y)/7/3x
3 answers
are you sure?
My apologies for the mistake in my previous response. Let's simplify the complex fraction correctly.
x + (4x/y) / 7/3x
First, simplify the numerator:
x + (4x/y) = x + (4x/y) = (xy/y + 4x)/y = (x + 4x)/y = 5x/y
Now, simplify the denominator:
7/3x = 7/(3x) = 7/(3x)
So, the simplified complex fraction is:
(5x/y) / (7/3x) = (5x/y) * (3x/7)
This simplifies to:
15x^2 / 7y
x + (4x/y) / 7/3x
First, simplify the numerator:
x + (4x/y) = x + (4x/y) = (xy/y + 4x)/y = (x + 4x)/y = 5x/y
Now, simplify the denominator:
7/3x = 7/(3x) = 7/(3x)
So, the simplified complex fraction is:
(5x/y) / (7/3x) = (5x/y) * (3x/7)
This simplifies to:
15x^2 / 7y